Mongol, nebo Mongolec? - HRDLIČKA , Milan (Bohemistyka, 2020)
The article describes how to form – with which sufix – inhabitants names (of states, of regions, of cities, etc.) correctly in contemporary Czech, for example how to use the name of inhabitant of Mongolia (Mongolian) correctly: Mongol, or Mongolec?